Preparation of athletes in cyclic sports taking into account the functional state of the external respiratory system and cardiovascular system - Omelchenko, O. S.; Afanasiev, S. M.; Savchenko, V. G.; Mikitchik, O. S.; Lukina, O. V.; Solodka, O. V.; Mischak, O. S. (Pedagogika, psichologika i mediko-biologiceskie problemy fiziceskogo vospitania i sporta, 2019)
The purpose of the study is to investigate the preparation of athletes in cyclic sports, taking into account the functional state of the external respiratory system and cardiovascular system (on the example of academic rowing). Material and methods. The study involved 13 athletes aged 19-22 years old. Athletes went for academic rowing in the Dnipropetrovsk region. A control and experimental group of 6 and 7 people were created, respectively. At the beginning of the experiment, there were no significant differences in fitness, physical development, and functional status between groups (p> 0.05). All study participants gave written consent to participate in the study. The studies were carried out at the specialized school of the Olympic reserve in rowing of the Dnepropetrovsk regional organization of the sports society "Ukraine", the regional school of higher sportsmanship. Medical and biological testing was conducted at the scientific laboratory of the Pridneprovsk State Academy of Physical Culture and Sports. Results . The dynamics of the indicators of the functional status of light weight rowers in rowing academic after using the experimental method was shown. It has been determined that under the influence of the experimental methods the cardiovascular system parameters underwent positive changes. These are the indices of variation range, vegetative rhythm index, pressure index, PWC170 test, maximal oxygen consumption, cardiovascular system response to exercise, recovery period. The introduced technique had a positive effect on the performance of athletes. In the experimental method, it was proposed to change the load in the complexes of exercises for the development of strength, maximum force, strength and speed endurance. The proposed technique of improving physical fitness was reflected in the formation of the plan of the annual training cycle. In accordance with the tasks of the period and mesocycles, exercises aimed at developing the leading qualities of light weight rowers were included. Conclusions. The analysis of the literature on the problem of research and generalization of the training of athletes in cyclic sports at the stage of preparation for higher achievements has revealed problematic issues. On the example of academic rowing these questions relate to the peculiarities of improving the process of physical preparation of rowers with light body weight, the peculiarities of functional state, the study of indicators of their physical and functional fitness. The dynamics of the functional state of the external respiratory system and cardiovascular system of athletes in cyclic sports (on the example of academic rowing) has been investigated. Some positive changes in the results of the vegetative index of the rhythm of the athletes were revealed. These indicators have approximated the value of the autonomic balance of athletes in the direction of parasympathetic regulation. There is a tendency to decrease the index of pressure. There was a decrease in heart rate, an increase in the maximum oxygen consumption and the level of physical performance.